Yours For A Song - Dana Suesse::::::::: (Robbins Music Corporation)
Piano and vocal score, 5 p. Featured in Billy Roses Aquacade at the New York Worlds Fair 1939 On cover: Featured in Billy Rose's Aquacade at the New York Worlds Fair 1939, staged by John Murray Anderson designed by Albert Johnson costumes by Raoul Pene Du Bois, Also on cover is illustration of Trylon and Perisphere Publishers advertisements on p.[2] and verso of last leaf.